(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
This paper proposes a hybrid system for secretly embedding images into the dithered multilevel image. Confident hybridizations between steganography and quantum encryptions are either rare in literature or suffer a poor effectiveness in secure communication. This paper scrambles and divides the secret image into groups to be embedded in the blocks of the cover image using three chaos algorithms. These are Lorenz map, Henon map, and Logistic map algorithms. The encryption of embedded images conducted using the quantum one-time pad. Results showed that the proposed hybrid system succeeded in embedding and combining images with quantum cryptography algorithms.